Impact of the histological phenotype of extrahepatic bile duct carcinoma - Okano, Kensuke (Mol Clin Oncol, 2018)
The classification of histological phenotypes was originally conceived for pancreatic intraductal papillary mucinous neoplasms. Recently, it has been introduced for extrahepatic cholangiocarcinoma. The aim of the present study was to clarify the associations between histological phenotype and clinicopathological features of extrahepatic cholangiocarcinoma, using 99 cases of surgically-resected extrahepatic cholangiocarcinoma. All cases were divided into one of two histological phenotypes: Biliary-type (BT; 56 cases, 56.6%) or metaplastic-type (MT; 43 cases, 43.4%). The clinicopathological features were compared between these two phenotypes. BT tumors exhibited significantly poorer differentiation, more frequent lymph node metastasis (BT vs. MT, 42.9 vs. 30.2%; P=0.042), more severe venous invasion (v2-3: BT vs. MT, 64.3 vs. 23.3%; P<0.001), and more severe perineural invasion (ne2-3: BT vs. MT, 78.6 vs. 48.8%, P=0.002). Furthermore, the overall (P=0.015) and disease-free (P=0.003) survival times were significantly decreased in patients with BT vs. MT tumors. In conclusion, extrahepatic cholangiocarcinoma with a BT phenotype has greater malignant potential, and may be an important predictive factor for poor prognosis.